The Development of Ethnoscience in Chemistry Learning in Indonesia: A Bibliometric Analysis of Literacy and Cultural Relevance - Vika Puji Cahyani; Dewiyanti Fadly (Universitas Cokroaminoto Palopo, 2024)
The main issue in this study is the lack of comprehensive understanding and mapping of the patterns and progress in ethnoscience research within the context of chemistry education in Indonesia. Investigating the patterns and advancements in ethnoscientific research in Indonesian chemistry education is the aim of this study. This study uses a bibliometric technique and is quantitative descriptive in nature. he stages include Selection of Topic and Research Objectives, Data Collection, Data Cleaning and Processing, Data Analysis, Data Visualisation, Interpretation and Discussion. Data collection was carried out by searching for journal articles indexed by Google Scholar through Publish or Perish (PoP) with the keyword ‘chemical ethnoscience’. Data from Publish or Perish (PoP) was filled in and completed in the author's keywords section manually using Mendeley desktop software then integrated into VOSviewer software for mapping. The results of the analysis of keyword mapping in Google Scholar indexed scientific articles from 2014-2024, it is known that in the last 10 years, there are 137 keywords that are interrelated. The top 7 keywords with the strongest links include: ethnoscience (40), chemical literacy (9), chemistry learning (6), chemistry (4), problem based learning (4), local wisdom (3), STEM (3). Recent keywords in chemistry education that are still rarely discussed in scientific articles are podcast-based ethnoscience, common knowledge construction, chemical bonding, CKCM learning model, Flipped Classroom, knowledge, references, implementation, culture, character values, ethnoscience-based chemistry, need analysis, independent curriculum, 4-D development.